2021
DOI: 10.2147/cmar.s300554
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Clinical Value of Circulating Tumor Cells as an Assisted Prognostic Marker in Colorectal Cancer Patients

Abstract: Background: Circulating tumor cells (CTCs) are cells that have been shed into the vasculature from a primary tumor and circulate in the bloodstream. It has been suggested that detecting CTCs could help the clinician to detect early metastasis or recurrence more effectively. This trial sets out to assess the detection and clinical value of CTCs as an assisted prognostic marker in patients with colon cancer and rectal cancer. Methods: A prospective cohort of patients with colorectal cancer (CRC) was enrolled fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The clinical utility of identifying circulating tumour cells in colorectal cancer patients has already been described by several authors [ 15 , 22 , 23 , 25 , 27 , 38 , 39 ]. However, current protocols for the isolation and characterisation of CTCs are mainly limited to the microscopic evaluation of one or two markers, compromising the ability to identify different CTC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical utility of identifying circulating tumour cells in colorectal cancer patients has already been described by several authors [ 15 , 22 , 23 , 25 , 27 , 38 , 39 ]. However, current protocols for the isolation and characterisation of CTCs are mainly limited to the microscopic evaluation of one or two markers, compromising the ability to identify different CTC subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…We defined CTCs as cells expressing cytokeratin (either bound to IsoFlux TM beads or not, as we pre-treated samples with papain to facilitate their analysis). Cut-off values of CTCs in non-metastatic colorectal cancer have been defined as between 1 and 5 cells in different studies [ 23 , 25 , 38 , 39 ]. However, as our methodology is more sensitive and efficient, we detected more CTCs per patient, and thus, cut-off values could be slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that high CTC counts correlated significantly with increased tumor stage with differences observed in T stage and N stages of the left and right hemicolon cancer. Furthermore, high CTC counts correlated with high tumor recurrence rate and worse prognosis indicating that change in CTCs counts could serve as a valuable tool for CRC prognosis [ 157 ]. Similarly, dynamic monitoring of CTC counts as a prognostic tool was investigated in a prospective phase II trial on153 CRC patients with resectable liver metastasis (LM).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Sebastian Hinz et al revealed that they used Ficoll extraction of mononuclear cells followed by CK20 RT–PCR to detect CTCs, with a detection rate of 30% [ 32 ]. In other investigations, CTCs were detected in almost 45% of CRC patients (TNM stage I–IV) [ 33 , 34 ]. Different detection methods may have different detection rates; nevertheless, standardized methods and novel techniques will enhance CTC detection in early malignancies [ 35 ].…”
Section: Main Textmentioning
confidence: 92%